1979
DOI: 10.2478/cttr-2013-0466
|View full text |Cite
|
Sign up to set email alerts
|

Composition Studies on some Varieties of Tobacco and their Smoke: I. Major Components in Smoke Condensate

Abstract: The relative proportions of the major smoke components and N-containing components in the semi-volatile phase and the non-volatile phase from some varieties of tobacco, i.e. flue-cured, Burley and Turkish tobacco, were determined. In flue-cured tobacco smoke, 2-furfural, 5-methylfurfural, 5-hydroxymethylfurfural and other carbohydrate pyrolysates, catechols and organic acids were present in higher concentrations than in the smoke from the other tobaccos. In Burley tobacco smoke, myosmine was present in much hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Thus, integrity of the Zilkey et al data set ( 60) is questionable. Matsushima et al quantified the MS deliveries/puff of six single blend component cigarettes, two each of fluecured, Burley, and Turkish tobaccos (61). The authors identified 10 MS smoke constituents which they considered have their origin from carbohydrate pyrolysis, and these are listed in Table 3.…”
Section: B Effect Of Sugars In the Tobacco Blend On Ms Smoke Acetalde...mentioning
confidence: 99%
“…Thus, integrity of the Zilkey et al data set ( 60) is questionable. Matsushima et al quantified the MS deliveries/puff of six single blend component cigarettes, two each of fluecured, Burley, and Turkish tobaccos (61). The authors identified 10 MS smoke constituents which they considered have their origin from carbohydrate pyrolysis, and these are listed in Table 3.…”
Section: B Effect Of Sugars In the Tobacco Blend On Ms Smoke Acetalde...mentioning
confidence: 99%
“…The combustion of cigarette tobacco filler during cigarette smoking creates an aerosol containing numerous chemical compounds (4,5). Among the thousands of reported chemicals generated during smoking are several specific classes of hazardous compounds that merit concern (3,4,(6)(7)(8)(9)(10). The International Agency for Research on Cancer (IARC) groups individual chemicals and chemical mixtures according to their carcinogenicity toward humans.…”
Section: Introductionmentioning
confidence: 99%
“…amino acid metabolism [1][2][3]. During tobacco curing, these SEs can release a broad range of aliphatic acids, including 3-methylvaleric acid and 3-methylbutyric acid, which substantially contribute to the sensory quality of tobacco smoke [4,5]. Some SEs have shown sensory, antibacterial, insecticidal, moisturizing, and plant growth-regulating properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose esters (SEs) constitute a significant class of compounds present on the tobacco surface, and they are entirely biosynthesized in glandular trichomes through sucrose and aliphatic acids produced via branched‐chain amino acid metabolism [1–3]. During tobacco curing, these SEs can release a broad range of aliphatic acids, including 3‐methylvaleric acid and 3‐methylbutyric acid, which substantially contribute to the sensory quality of tobacco smoke [4, 5]. Some SEs have shown sensory, antibacterial, insecticidal, moisturizing, and plant growth‐regulating properties [6–8].…”
Section: Introductionmentioning
confidence: 99%